Islam dan Kekerasan terhadap Perempuan - Busriyanti, Busriyanti (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2012)
Religious understanding of the texts and doctrines towards women issues has not come to the final. Cultural construction and professional religious interpretation toward religious scripts also contribute on the woman issues especially in relation with unbalanced relationship between man and woman. Many religious interpretations then put women in secondary level with men as the result that they, women, are seen as men belonging that can be authoritatively subjected as much as men wants, including of violence. Up to this time, the domestic violence happens with regards to the women as the victims, and it is supposed that religious understanding is taking part in contributing the “act of violence” towards women’s existence. So that religion, in this case, remains problematic in shaping the social construction of men and women relations. This article aims to explore more causes of women’s violence and attempts to scrutinize religious interpretation on the texts of gender and family issues. This article argues that religious institution and religious education have big role to shape the contemporary religious understanding towards women’s life; and both religious institution and religious education may also become the indispensable foundation of empowering woman by giving new interpretation of the women public space.